The Historic Elimination of Mother-to-Child HIV and Syphilis Transmission in Puerto Rico - Vermund, Sten H.; Febo, Irma (Puerto Rico Health Sciences Journal, 2021)
The elimination of HIV and syphilis from Puerto Rico as per metrics of the World Health Organization has been achieved despite continued HIV risk and high background prevalence. Excellence in antenatal services and screening, deployment of antiretroviral and penicillin syphilis therapies, and proper follow-through with mothers and infants has yielded success even as control of infection overall remains elusive. We highlight the context of this achievement in our editorial to accompany the article: “Elimination of the Perinatal Transmission of HIV and Syphilis in Puerto Rico and Sustained Success since 2007: Convergence of Science, Women-Centered Care, and Policy”.